Nutrient Management for Optimizing Fodder Production of Sorghum – A Review - Prajapati, Brajkishor; Shrivastava, Atul Kumar; Sarvade, S.; Agrawal, S. B.; Solanki, R. S. (International Journal of Bio-resource and Stress Management, 2023)
An area under cultivation of fodder crops has almost remained static (8.3 million ha) for the last 3 decades and area under permanent pastures has been declining over the years. Whereas, uncontrolled overgrazing reduced productivity of permanent pastures. Overgrazing also affect the soil bio-physic-chemical properties. The situation is further aggravated due to increasing human population and preferential need for food and growing commercial crops. In India, supply of forage has always been a limiting factor for enhancing livestock production. Demand of green and dry fodder continuously increasing as enhancing country’s livestock population. The gap in feed and forage supply, however, can effectively be reduced through integrated crop management practices with greater emphasis on nutrient management in forage crops. Application of nitrogen increases crude protein, digestible dry matter content and metabolic energy. Growth attributes with respect to plant height, stem diameter, Leaf Area Index (LAI) and number of basal node tillers increased with increase of phosphorus application levels. Application of micronutrients improves enzymatic activities and it leads to increase growth and yield of the fodder sorghum. Review regarding the use of adequate and optimum dose of nutrients especially nitrogen, phosphorus and micronutrients are of prime concern for the fodder sorghum crop in India. Keeping these points in view, the literature reviewed pertaining to the nitrogen, phosphorus and micronutrients in this crop to obtain higher biomass and good quality fodder production.